Reading in Public Libraries: Space, Reading Activities, and User Profiles - Sequeiros, Paula (Qualitative Sociology Review, 2013)
This single case research was developed within a public library in Porto, Portugal, Biblioteca Municipal Almeida Garrett. Its main objective was to understand how public library readers interact with space, the Internet technology, and reading resources, and how these interactions shape the representations of what a public library is. This case was chosen because the library has a recent and renowned building, high reader use levels, and Internet access. The design of user profiles was an intermediate step, and then a partial result in the process of understanding provision and appropriation of technology, space, and reading resources (all media and supports) in a specific context. The construction of these profiles is presented and discussed in this paper. A qualitative, single case study was designed according to Burawoy’s Extended Case Method, departing from the framework of several theories – Feenberg and Bakardjieva’s approach to Internet uses, Lefèbvre and Certeau’s approach on space – and some library users and studies of Internet user profiles – by Rodrigues, Bakardjieva, and by other authors. A theoretical, diversified sample was constructed. User profiles were designed as a way of depicting common reading practices by grouping readers’ characteristics according to Internet, space, and bibliographical resource usage. Along with this usage, social demographics, motivations, meanings, and feelings were enquired about to construct a thick narrative. Observation of all forms of reading practices, in-depth interviews, informal conversations, children’s drawings, photography, and an architectural and social analysis of the building were used. The library has diversified uses, tied to present-day everyday life conditions, and its space and management style are flexible enough to allow for different user appropriations. As to the general reading atmosphere, high satisfaction was reported, and the most appreciated features of social and architectural space were signaled by readers. User profiles reflect diversified usage modes, diverse relations to space, to Internet and bibliographic resources, and to other users. Both the theoretical framework and the selected methodology proved fruitful for the intended purpose. These readers’ profiles may provide a tool to understand and manage public library services, given the adequate fittingness. The same may be said about readers’ evaluation of space, in general, or, specifically, about space appropriations, and, above all, about the production of stimulating reading atmospheres